Global knowledge hubs and their impact on firm performance : the perspective of maritime Singapore - Tan, Beverly Charis Shi Yun (Nanyang Technological University, 2015)
Industrial clusters are vital to governments and businesses as they purportedly enhance competitive advantage, economic growth and firm performance. With the proliferation of the knowledge-based economy, clusters have become increasingly knowledge-based, which led to the emergence of the global knowledge hub (GKH) concept that has already been applied in maritime policy. The GKH concept, however, remains conceptually nebulous due to a scarcity of existing literature, particularly in the maritime arena. This study thus develops a generic GKH conceptual model, and subsequently, investigates its impact on firm performance in the context of Singapore’s maritime industry. Through data obtained from 16 in-depth interviews and 203 survey responses, the proposed GKH model was empirically validated. The GKH was also discovered to positively and significantly impact firm performance, with social capital and absorptive capacity as mediators. Content and thematic analyses were employed to evaluate interview data, whilst PLS-SEM was utilized for analysing survey data.